WORK OF VIRTUAL LABORATORIES OF ORGANIC CHEMISTRY FOR ACADEMIC LYCEUMS - D.O. Sadikov (Next Scientists Conferences, 2025)
The work of virtual laboratory of organic chemistry, creative and academic lyceum in LabVIEW graphic programming environment is described. In particular, information is provided on the production of acetylene from calcium carbide and the process of synthesis of bromethane.